Frequency of Anterior Inferior Cerebellar Artery Vascular Loops Using CISS Sequence on 3.0T MRI in the Otologic Symptomized Patients - Humaira Riaz, Zainab Riaz, Ania Javed, Fizza Batool, Syeda Sanam Zahra, Sana Afzal Alvi (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To estimate the frequency of vascular loops in the anterior inferior cerebellar artery in the otologic symptomized patients using CISS sequence on 3.0 Tesla MRI” in Pakistani populations. Methodology: Cross sectional descriptive study was conducted in Armed Forces Institute of Radiology and Imaging, Military Hospital Rawalpindi from 12th April 2019 to 11th October 2019. One hundred patients of both genders between age of 20-60 years were presented with otologic symptoms i.e. tinnitus, dizziness and hearing loss (unilateral/bilateral) and advised MRI brain. Patients with any diagnosed arterial, venous and arterio-venous cause of otologic symptoms, severe claustrophobia and with internal cardiac pacemakers or any other metallic foreign body were excluded. Patients were undergone MRI brain on 3.0 Tesla. TIWS, T2WS and CISS sequences were taken along with post-contrast T1WS images. Results: There was 20 to 60 years of patients range of age having mean age of 38.38±12.05 years and majority of patients 65% between 20-40 years. There were 53(53%) males and 47(47%) females and having 1.2:1 ratio of male to female. Frequency of anterior inferior cerebellar artery vascular loops in the otologic symptomized patients using CISS sequence on 3.0 Tesla MRI was seen in 59(59%) patients. Conclusion: The frequency of anterior inferior cerebellar artery vascular loops in the otologic symptomized patients using CISS sequence on 3.0 Tesla MRI is very high. Keywords: Anterior inferior cerebellar artery vascular loops, Magnetic resonance imaging, Otologic symptoms